Supporting women scholars' paths to academia: An examination of family-friendly policies of public affairs doctoral programs. (3rd July 2021) - Bodkin, Candice Pippin; Fleming, Casey J.
ABSTRACT: Despite earning roughly half the doctoral degrees in public administration, women remain underrepresented in public affairs programs, particularly in senior positions. Studies describe a leaky pipeline from which women exit the academic career, and there is growing interest in removing administrative, structural, and cultural barriers facing women scholars as well as supporting healthy career-life balance. Considerable research examines family-friendly workplace initiatives for faculty, yet little attention is paid to the availability of such policies for students. Drawing from archival and survey data, this study investigates the availability of specific family-friendly policies for doctoral students of public affairs programs in the U.S., potentially effective human resource management approaches to addressing exit points between graduate school and faculty membership. Findings reveal inconsistent and relatively insubstantial provision of formal policies; however, informal workarounds appear to be a common strategy for meeting the needs of graduate students who become parents during doctoral studies.